DEVELOPMENT OF A REAL-TIME RT-PCR-BASED TEST PANEL FOR ASSESSMENT OF CYTOKINE PROFILE IN MONONUCLEAR CELLS FROM BLOOD AND SYNOVIAL FLUID IN RHEUMATOID ARTHRITIS - D. Yu. Trofimov; O. V. Burmenskaya; E. I. Bateneva; L. P. Alexeev; E. L. Nasonov; E. N. Alexandrova; A. A. Novikov (Медицинская иммунология, 2014)
Abstract. An imbalance between pro- and anti-inflammatory cytokine synthesis plays a crucial role in pathogenesis of rheumatoid arthritis (RA), including erosive joint lesions. Differences in cytokine profiles of RA patients are sufficiently investigated. However, possible interrelations between cytokine profile, immune inflammation, RA progression, and the disease prognosis require further investigations. Due to active search for novel targets in anti-cytokine therapy of RA, evaluation of cytokine levels in peripheral blood and synovial joint fluid remain quite relevant. Therefore, novel methods aimed to determine mRNA expressed by cytokine genes are thought to be promising. Our research was intended to develop test systems for quantitative determination of mRNAs for the following cytokines: TNFα, IL-1β, IL-6, IL-8, IL-17, IL-15, IL-10, IFNγ, IL-4, IL-2. Present article concerns specificities of the developed test systems, description of their technical principles, as well as comparative studies of cytokine gene expression in peripheral blood and synovial joint fluid in RA patients. (Med. Immunol., 2008, vol. 10, N 6, pp 563-570).